Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.4172/2161-1076.s12-011
|View full text |Cite
|
Sign up to set email alerts
|

A Report on a 7-year Follow up of the Surgical Management with PRGF®- ENDORET® of Oncologic Patients Affected by Intravenous Bisphosphonate Related Osteonecrosis of the Jaw

Abstract: Mozzati et al., Surgery 2013, S12 http://dx.doi.org/10.4172/2161-1076.S12-011 Research ArticleOpen Access AbstractBRONJ is an important complication in bisphosphonate therapy that dramatically influences the patient's quality of life and requires immediate intervention. The situation is worsened by the fact that its management is still an open issue, with no definitive standard of care. The aim of this paper is to present the short, middle and long term (7 years) results of surgical treatment of 32 BRONJ case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 26 publications
(27 reference statements)
1
12
0
Order By: Relevance
“…ZA+PRGF: treatment with zoledronic acid + PRGF). *Statistically significant differences compared to the control and ZA+PRGF treatments (p < 0.05) BRONJ has been reported, thus improving wound healing, enhancing vascularization and osseous and epithelial tissues regeneration [11,12,40,41]. The in vitro findings obtained in this study may be behind of these good clinical data.…”
Section: Discussionsupporting
confidence: 53%
“…ZA+PRGF: treatment with zoledronic acid + PRGF). *Statistically significant differences compared to the control and ZA+PRGF treatments (p < 0.05) BRONJ has been reported, thus improving wound healing, enhancing vascularization and osseous and epithelial tissues regeneration [11,12,40,41]. The in vitro findings obtained in this study may be behind of these good clinical data.…”
Section: Discussionsupporting
confidence: 53%
“…This led to a final selection of 13 studies [42][43][44][45][46][47][48][49][50][51][52][53][54]. Among these, three studies had parts which had to be excluded as they did not meet inclusion criteria or met the exclusion criteria: one [43] had a part which treated unconventional therapies; one [50] had a part in which outcomes were not evaluated according to stage at diagnosis; one [51] had a part in which treatment outcome was evaluated on…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies had a retrospective design [42-46, 48, 50, 53, 54] and four were prospective studies [47,49,51,52]; one was single-blinded [45], whereas for the other 12, these data were not available. Five studies were conducted in private practice [46,50,51,53,54], whereas five studies were performed in a university setting [43,44,[47][48][49]. Only one study was conducted both in private practice and in university [45].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Even better improvement outcomes were seen with PRF (platelet-rich fibrin) with studies carried out by Dincă et al [ 49 ] and Kim et al [ 50 ] with significantly better recovery and less delayed healing signs. Studies carried out by Mozzati [ 51 , 52 ] showed that treatment with PRGF (plasma rich in growth factors) showed the best after-effects with no complications or recurrences during the follow-up. Preventive and diagnostic strategies are important in avoiding implant-related BRONJ, according to Marx et al [ 53 ] and Kunchur et al [ 54 ], CTX values of 150 pg/mL and more greatly reduced the risk of osteonecrosis occurrence.…”
Section: Discussionmentioning
confidence: 99%